Existence of minimizers for causal variational principles on compact subsets of momentum space in the homogeneous setting - Langer, Christoph (Calculus of variations and partial differential equations, 2022)
We prove the existence of minimizers for the causal action in the class of negative definite measures on compact subsets of momentum space in the homogeneous setting under several side conditions (constraints). The method is to employ Prohorov’s theorem. Given a minimizing sequence of negative definite measures, we show that, under suitable side conditions, a unitarily equivalent subsequence thereof is bounded. By restricting attention to compact subsets, from Prohorov’s theorem we deduce the existence of minimizers in the class of negative definite measures.